Literasi Pendidikan Fiqih Berkeadilan Gender dalam Mencegah Kekerasan Seksual di Pondok Pesantren Darussalam Blokagung Banyuwangi - Chanifah, Nur; Samsudin, Abu (Faculty of Cultural Studies, Universitas Brawijaya, 2025)
Recently, cases of sexual violence in Islamic boarding schools have become very worrying. According to the National Commission on Violence Against Women, there will be 3,303 cases of gender-based violence in 2023. Service institutions reported 6,305 cases, and the Religious Justice Agency (Badilag) recorded a much higher number, namely 279,503 cases. Thus, gender-based sexual violence is very worrying. Fiqh literacy basically has a very important role in preventing sexual violence. But unfortunately, fiqh literacy in Islamic boarding schools so far has not received much attention, because they are considered knowledgeable. For this reason, the Brawijaya University Faculty of Law service team carries out outreach and counseling to students regarding the importance of studying jurisprudence with gender justice. This activity was attended by around 100 female students at the Darussalam Islamic Boarding School in Blokagung, Banyuwangi. This activity had a positive impact on students' understanding of gender-equitable jurisprudence. The students increasingly understand their position and relationships with the opposite sex, so that they are not easily deceived by the advances of individuals or perpetrators of sexual violence. In this way, it is hoped that the number of sexual violence in Islamic boarding schools will decrease, even to zero.